THE MORPHOLOGY OF THE GORONTALO FOLKLORE PERANG PANIPI: A STUDY OF VLADIMIR PROPP'S NARRATOLOGY - Jafar Lantowa (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
This study examines the morphology of the Gorontalo Folklore of Perang Panipi based on Propp's narratological theory. The purpose of this study was to determine the structure of the folklore of Perang Panipi. This study employed a qualitative method with narratology structural analysis. Data were collected using a literature study (documentation technique) and then analyzed using structural analysis techniques. The analysis was first carried out on the findings from heuristic and hermeneutic reading, especially on story morphemes, which were Vladimir Propp's 31 functions of actors who build stories. Furthermore, it is entered into the characters' spheres of action which will clarify the characters' behavior in the story. The results showed twelve main narrative functions, three story patterns, and four spheres of action in the Panipi War folklore.